Influence of the Home Linguistic Environment on Early Language Development. (October 2017) - Brito, Natalie H.
Approximately 15.5 million children in the United States (21%) live in impoverished households, with child poverty rates highest among Black, Hispanic, and American Indian children. Growing up in a socioeconomically disadvantaged environment is associated with substantially worse health and impaired psychological, cognitive, and emotional development throughout the life span. Socioeconomic status (SES) has a robust association with language development—across different language outcomes, across different ethnic and language-exposure groups, as well as within these groups. This review examines pathways for SES disparities in language skills emerging early in development and contributing to later gaps in school readiness and academic achievement.